Factors Affecting Recurrence of Idiopathic Granulomatous Mastitis: A Systematic Review - Asieh Sadat Fattahi; Ghasem Amini; Fatemeh Sajedi; Hassan Mehrad-Majd (Hindawi-Wiley, 2023)
Idiopathic granulomatous mastitis is a rare and benign disease that primarily affects young women of reproductive age. Various factors have been suggested as possible causes, including pregnancy, breastfeeding, history of taking birth control pills, hyperprolactinemia, smoking, and history of trauma. Due to unknown etiology, opinions on its treatment have varied, resulting in differing recurrence rates and side effects. Therefore, conducting a comprehensive systematic review and meta-analysis can aid in understanding the causes and recurrence of the disease, thereby assisting in the selection of effective treatment and improving the quality of life. A systematic literature review was conducted using predefined search terms to identify eligible studies related to risk factors and recurrence up to June 2022 from electronic databases. Data were extracted and subjected to meta-analysis when applicable. A total of 71 studies with 4735 patients were included. The mean age of the patients was 34.98 years, and the average mass size was 4.64 cm. About 3749 of these patients (79.17%) were Caucasian. Patients who mentioned a history of pregnancy were 92.65% with 76.57%, 22.7%, and 19.7% having a history of breastfeeding, taking contraceptive pills, and high prolactin levels, respectively. Around 5.6% of patients had previous trauma. The overall recurrence rate was 17.18%, with recurrence rates for treatments as follows: surgery (22.5%), immunosuppressive treatment (14.7%), combined treatment (14.9%), antibiotic treatment (6.74%), and observation (9.4%). Only antibiotic and expectant treatments had significant differences in recurrence rates compared to other treatments (p value = 0.023). In conclusion, factors such as Caucasian race, pregnancy and breastfeeding history, and use of contraceptive hormone are commonly associated with the disease recurrence. Treatment should be tailored based on symptom severity and patient preference, with surgery or immunosuppressive options for recurrence.